Decreased frequency of a novel T‐lymphocyte subset, CD3+CD4−CD7+CD57− T cells, in hepatitis B virus‐related end‐stage liver disease might contribute to disease progression. Issue 1 (28th September 2022) - Yu, Xueping; Zheng, Yijuan; Zeng, Dawu; Zhou, Yongjun; Sun, Jian; Su, Milong; Zhang, Huatang; Zheng, Minhui; Huang, Zhipeng; Lin, Wenwu; Mao, Richeng; Zhang, Jiming; et al.
Abstract: CD7 and CD57 are related to the differentiation and functional stages of CD8 + T cells. However, the role of their combined presence in CD8 + T cells in patients with chronic hepatitis B virus (HBV) infection, especially those with end‐stage liver disease, remains unclear. Blood samples from healthy volunteers and patients with chronic hepatitis B were analyzed via Luminex assay and ELISA to measure plasma cytokine levels. Further, recombinant IL‐22 was used to stimulate peripheral blood mononuclear cells from healthy volunteers, and the frequency of CD3 + CD4 − CD7 + CD57 − T cells and apoptosis rates were investigated via flow cytometry. Patients with end‐stage liver disease, particularly those with acute to chronic liver failure, showed decreased CD3 + CD4 − CD7 + CD57 − T cell frequency. Furthermore, the prevalence of CD3 + CD4 − CD7 + CD57 − T cells was negatively correlated with disease severity, prognosis, and complications (ascites). We also observed that IL‐22 promoted apoptosis and brought about a decrease in the number of CD3 + CD4 − CD7 + CD57 − T cells in a dose‐dependent manner. CD3 + CD4 − CD7 + CD57 − T cells displayed a B and T lymphocyte attenuator (BTLA) high CD25 high CD127 high immunosuppressive phenotype and showed low interferon‐γ, tumor necrosis factor‐α, granzyme A, and perforin expression levels. The present findings will elucidate the pathogenesis of HBV‐related end‐stage liver disease and aid the identification of novel drug targets.